CRAPHIC FACTORS IN THE CONSTRUCTION AND OPERATION OF LIBYAN PETROLEUM PORTS - Brown, Robert W. (Dirasat in Economics and Business, 1966)
Since September 12, 1961 crude oil has been flowing out of Libya at an increasing pace which has made petroleum history. Libyans almost everywhere in the country have experienced the impact of the oil boom. The cities of Tripoli and Benghazi have come alive with new construction, and the vast reaches of the desert have become streaked with vehicle tracks and dotted with drilling rigs. Esso's Marsa el Brega, Oasis' Es Sider and Mobil-Gelsenberg Amoseas' Ras Lanuf are now the three leading ports of Libya by value and tonnage of exports; yet seven years ago not a sign of a ship or a ship facility marked their sites. The wide dispersal of the Sirtica oil fields (Gialo is 330 kilometers eastof Dahra) suggests that at least two gathering systems are needed for efficient distribution of the oil. The fact that there are three is due mainly to the provisions of the Libyan Petroleum Law. By fragmenting concessions among nineteen companies or groups of companies,¹ by encouraging active exploration through the territorial cession clause, and by levying a premium surface rent of £ 2500 per 100 square kilometers on concessions with established commercial fields, the law has spurred oil companies to construct pipelines and terminals to serve their own needs at the earliest possible date. Esso planned Libya's first pipeline in response to the discovery of the Zelten field, officially labeled as commercial on September 1, 1959.2 Oasis' first commercial field was Dahra, the official date being June 28, 1960, and the company started a second pipeline 180 kilometers to the west. Amoseas' Beda field and Mobil. Gelsenberg's Hofra were commercial finds as of April 1, 1963, long after the Esso and Oasis systems had commenced operations. Utilizing a clause in the petroleum law3 that provides for one company's sharing another's pipeline and terminal if the capacity is available, Mobil. Gelsenberg and Amoseas quickly built spur lincs to the nearby Oasis network and exported through Es Sider. But their discoveries merited the insurance of an individual system, which began to emerge in a form almost precisely like that of Oasis and at no point more than forty kilo. meters away from it. The Libyan pipeline pattern has become even more intriguing with the 423kilometer sweep of Oasis lines into Concession 59 E, passing within thirty kilometers of Esso's line from the new Jebel field to Zelten.